Engineering evaluation of the Portland Cement Association's book : '' design of multistory reinforced concrete buildings for earthquake motions'' (Blume, Newark, Corning) - Degenkolb, Henry J. ([s. n.], 1963)
An evaluation of Blume, Newark, and Corning's book " Design of multistory reinforced concrete buildings for earthquake motions" published by Portland Cement Association.